Kinematic Modeling of 3P2R Welding Robot Based on D-H Parameters. Issue 1 (1st March 2022) - Chen, Hongtang; Ma, Haijun; Jiang, Hongli; Lv, Shenjin; Li, Yong; Liu, Heshan
Abstract: To meet the demand of different vehicle models welding task, as well as lower the cost of specialized welding facility, a kind of 3P2R arc welding robot has been developed and SolidWorks is used to set up the Three Dimensional (3D) solid model. The developed robot includes 3P2R body, controller, and a welding power supply. The direct kinematical model and inverse solution have been worked out basing on Denavit-Hartenberg (D-H) method, and the direct kinematical model and inverse solution are verified by experiment. This robot could also be used to burring or spray field with the actuator changed.